(untitled) (International Journal of Engineering and Computer Science, 2017)
This is the model for displaying notices in colleges on electronic notice board by sending messages in form of SMS through mobile; it is a wireless transmission system which has very less errors and maintenance. The hardware board contains microcontroller AT89c52 at the heart of the system. The microcontroller is interfaced with GSM Modem via MAX232 level convertor. It is used to convert RS232 voltage levels to TTL voltage levels and vice versa. The hardware also has a 64K EEPROM chip AT24C64. This EEPROM is used to store the timings and messages to be displayed. Hardware also contains a real time clock DS1307 to maintain track of time. A 16x2 Character LCD display is attached to microcontroller for display. Microcontroller coding will be done using Embedded C and Kiel. PC Coding will be done using Visual Basic. Multiple Users are authorized to update notices on the electronic notice board by providing them password. We can use a PC with an administrator for monitoring the system